Utilização do Moodle como ferramenta de gestão e comunicação entre as coordenações de curso de graduação do Centro de Ciências Sociais e Humanas da UFSM - Farias, Alice Lameira (2019)
The present study, developed within the research line Management of Networked Educational Technologies, of the Graduate Program in Networked Educational Technologies (PPGTER) of the Federal University of Santa Maria (UFSM), approaches there search about the applicability of Moodle as a tool of Academic Management. Whit this, pretends to build a form of communication with interaction between undergraduate secretariats of the Center for Social and Human Sciences of the Federal University of Santa Maria. Firstly, a literature review was conducted on the perspectives of several authors who presents concepts that facilitate the identification of the limit sand possibilities of Moodle insertion and application as a facilitating Academic Management tool for communication and sharing files and materials that optimize the administrative management among coordinations. It follows with the analysis of the application and insertion of this Academic Management tool, approaching the communication between secretaries and Coordinators of undergraduate courses. The dissertation is organized into six chapters that address from the contextualization, conceptualization and analysis of applicability and insertion of Moodle among the agents involved. The Methodological and Theoretical Referrals present authors such as Castells (2002), Levy (2007), Torres & Irala (2014), Lima & Satini (2008), Cardoso (2003), among others who reflect on this subject and seek education al technologies as an assist Academic Management. In addition to deepening the study on the importance of new resources, increasingly present in the context of coordination management. In this case, it was verified that the Moodle Virtual TeachingLearning Environment (AVEA), can present as advantages its use in Education beyond the classroom and seek the understanding that there are tools that can contribute in the relations hip between the agents involved in the context of undergraduate course coordinations. For such purpose, there search was based on a set of variables that include the study on interaction and collaborativity in the Academic Management processes. It is concluded that the applicability of Moodle as a Management and Communication Tool is important and able to assist in the exchange and search of information regarding the processes and administrative routines of a coordination. The final product was the development of a new functionality for the Moodle environment, created with the collaborative participation of the Undergraduate Secretaries and Coordinators, to be used by the CCSH Undergraduate Course Coordinators, and as a basis for other sectors to research about applicability of Moodle as an academic management tool, promoting communication between these sectors at the University. It should be noted that it can be used for research and as a basis for application in other teaching units of UFSM.